GAMBARAN SEL EPITEL MUKOSA RONGGA MULUT PADA PEROKOK AKTIF DENGAN DURASI LAMA MEROKOK - Roro Ilmi Walzismi Saragih; Yeni Rahmawati; Rosmita Anggraeni (Jurnal Insan Cendekia, 2026)
Long-term smoking habits can lead to disease. The oral cavity is easily exposed to the detrimental effects of cigarette smoke. Hot smoke that continuously blows into the oral cavity can cause the oral cavity to become dry, which can lead to the emergence of oral diseases. The purpose of this study was to examine the relationship between smoking duration and changes in oral mucosal epithelial cells. This study was a quantitative, analytical observational study using a case-control method. This study involved 15 smokers and 15 non-smokers selected based on inclusion and exclusion criteria in motorcycle community in Yogyakarta in April 2025. Each respondent’s oral epithelial cells were taken with a cytobrush and subjected to Papanicolaou staining. Data were analyzed using Chi Square. The result showed that the majority of smokers experienced changes in epithelial cells. The Chi Square test showed a significant relationship between smoking duration and changes in epithelial cells (P<0,001). This study demonstrated a significant relationship between smoking duration and changes in the morphology of oral mucosal epithelial cells in active smokers. Future researchers are advised to measure the diameter of the cells nucleus and cytoplasm, as well as examine genotoxic markers an examine p53 protein expression to support cytological analysis. Suggestions for respondents and the community are to reduce smoking an replace smoking habits with healthier activities.